PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Firdaus Firdaus; Rahmi Widyanti; Khuzaini Khuzaini (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2017)
This study aims to, prove significant influence motivation partially on employee performance, proving significant effect partially to the Work Environment Employee Performance, and prove the significant influence of Motivation and Work Environment simultaneously against South PT.Tanjung Employee Performance Makmur Jaya South Kalimantan.Methods of analysis using multiple linear regression equation .Populasi in this study were all fixed karwayan South PT.Tanjung Makmur Jaya South Kalimantan .Sampel research as much as 67 .Pengujian partially Variables Influence Motivation (X1) the Employee Performance is equal to 17,182, thus, the hypothesis that motivation berpengauh positive and significant impact on Employee Performance South PT.Tanjung Makmur Jaya South Kalimantan proved acceptable. Working Environment Variables Influence (X2) to the environment variable t value is equal to 9,785, thus partially the environment has a significant impact on employee performance South PT.Tanjung Jaya Makmur South Kalimantan proved acceptable. Effect of Motivation and Work Environment Variables simultaneously towards employee performance with the result of 178,391 F count larger than F table 3,140, thus simultaneously Motivation and Work Environment positive and significant impact on Employee Performance PT. South Tanjung Jaya Makmur South Kalimantan proved acceptable.Keywords: Motivation, Work Environment and Employee Performance.